Aquaporin 1, Aquaporin 3 and Aquaporin 5 expression and EGFR mutation in malignant pleural mesotheliomas: an imunohistochemical and molecular study - Ulaş Alabalık; Gül Türkcü; Ayşe Nur Keleş; İbrahim İbiloğlu; Zuhat Urakçı; Hüseyin Büyükbayram (Biotechnology & Biotechnological Equipment, 2017)
Malignant pleural mesothelioma is a rare and fatal malignancy. This disease is, unfortunately, at its advanced stage when it is diagnosed. Survival time is usually not more than a few months. The aim of this study was to analyse the expression of Aquaporin 1, Aquaporin 3 and Aquaporin 5 in malignant pleural mesotheliomas and to explore the relationship of these levels of expression with epidermal growth factor receptor (EGFR) gene mutation and prognostic parameters. In this study, 60 cases diagnosed as malignant pleural mesothelioma among the pleural biopsy materials in the archives of the Pathology Department of Medical Faculty of Dicle University in 2003–2013 were evaluated. The tissues were stained immunohistochemically with antibodies against Aquaporin 1, Aquaporin 3 and Aquaporin 5, and the existence of EGFR mutation was investigated in the tissues by real-time polymerase chain reaction (PCR). The obtained results showed expression of Aquaporin 1, Aquaporin 3 and Aquaporin 5 in varied amounts in malignant pleural mesotheliomas. However, no significant relation was obtained thus far between the expression levels of these aquaporins and the prognostic parameters. No mutations were detected in the EGFR gene exons 18–21 by using real-time PCR. It could be suggested that although Aquaporin 1, Aquaporin 3 and Aquaporin 5 are expressed in malignant pleural mesothelioma, they do not have any effect on the prognostic parameters. Mutations in different domains of EGFR gene, other than exons 18–21, should be sought to develop new targeted treatments.